posted by Rachelle on .
Hi! I have a few questions about Factoring Quadratic Expressions.
My first one is 12x^2+x=6. How would you facor that?
My second is how would x^4-1 equal the answer 1(x^4-1)(x^2=1)(x^2-1)?
Finally, how would you factor something such as -3x(x+2)-8(x+2), when there is no common factor other than one?
Thank you so much for your assistance! :)
12 x^2 + x - 6 = 0
I solved the quadratic and got 2/3 and -3/4 so then tried
x^4-1 is difference of two squares
for 12x^2+x=6 write is as
12x^2+x-6 = 0
then (3x-2)(4x+3) = 0
x^4-1 factors to
(x^2 -1)(x^2 + 1)
for -3x(x+2)-8(x+2) you should see that ((x+2) is a common factor, so
sure there is a common factor -- (x+2)